Learning Pantun through Character-Educated Smart Pantun Web by Utilizing Local Wisdom - Sati Sati; Kuntoro Kuntoro (UM Purwokerto Press, 2023)
The use of digital technology that is increasingly widespread in the world of education, spurred researchers to present the Pantun Learning Website presented in www.samrtpantun.com named